Emergence of pneumococcal 19A empyema in UK children. Issue 12 (16th October 2012) - Thomas, Matthew F; Sheppard, Carmen L; Guiver, Malcolm; Slack, Mary P E; George, Robert C; Gorton, Russell; Paton, James Y; Simmister, Clare; Cliff, David; Elemraid, Mohamed A; Clark, Julia E; Rushton, Stephen P; et al.
Abstract : Introduction: Invasive pneumococcal disease due to serotype 19A has become a major concern, particularly in the USA and Asia. We describe the characteristics of pneumococcal serotype 19A related empyema and changes in its incidence in the UK. Methods: Data from paediatric empyema patients between September 2006 and March 2011 were collected from 17 respiratory centres in the UK. Pneumococcal serotypes were identified as part of the Health Protection Agency enhanced paediatric empyema surveillance programme. Results: Four serotypes accounted for over 80% of 136 cases (Serotype 1 : 43%, 3 : 21%, 7 : 11% and 19A:10%). The incidence of empyema due to serotype 19A quadrupled from 0.48 (0.16–1.13) cases per million children in 2006/2007 to 2.02 (1.25–3.09) in 2010/2011. Severity of disease was significantly increased in children with 19A infection when compared to other serotypes. Conclusions: The incidence of empyema due to pneumococcal serotype 19A infection has increased significantly and is associated with substantial morbidity.